Medical Affairs in Pharmaceutical Companies and Related Pharmaceutical Regulations in Japan - Maeda, Hideki (Frontiers in Medicine, 2021)
Medical affairs has rapidly attracted a great deal of attention in recent years in Japan, but is also often misunderstood or poorly understood within healthcare fields in Japan. In the United States, the function of medical affairs has been established for a long time, whereas its history in Japan is relatively short. Around in 2012, many incidents in clinical trials arose related to questionable ties between medical doctors and the sales departments of pharmaceutical companies. These incidents undermined confidence in clinical trials in Japan, and triggered the enforced separation of sales departments from the conduct of post-marketing clinical trials and evidence generation. This resulted in the establishment of independent medical affairs departments from sales departments in pharmaceutical companies operating in Japan. Due to this short history in Japan, the roles and responsibilities of medical affairs vary between companies in Japan. Medical affairs departments aim to fulfill unmet medical needs through the generation of scientific evidence and thus to deliver scientific value to key stakeholders and patients. Individuals working in medical affairs need to be able to engage in scientific exchange activities with key opinion leaders independent of sales departments. Through these activities, medical affairs departments ensure that patients receive optimal medical care. Medical affairs in Japan is still developing and its roles, responsibilities, and functions are improving. I have looked back into the history of medical affairs in Japan and discuss the current status and future perspectives of medical affairs in Japan.